Catappa Tea Enterprise - Awang Muslaini, Nooreffariza; Sappari, Halimatun Sohanah; Chu, Bibiana; Abdul Rashid, Nur Hazwani; Musneh, Siti Noraisah (2009)
We are the one of business that produces catappa tea product after Jabatan Penyelidikan Pertanian Sandakan introduces this herb product to us. Our business was located at Industrial Zone KKIP Selatan, Kota Kinabalu, Sabah because the area is proximity to our product resources, proximity to the facilities, low cost rent and strategies place to sell our catappa tea product to the suppliers. Our business opportunity begins with the existence of various customers' needs and wants for our products. As society becomes more affluent, there will be more human needs and wants to be fulfilled. Our product is something that possesses a physical form that is required to fulfill human wants directly and indirectly and it also come out for the human needs to be fulfilled which is as medicinal for such illnesses.